Creating psychological safety in interprofessional simulation for health professional learners: a scoping review of the barriers and enablers. - Lackie, Kelly; Hayward, Kathryn; Ayn, Caitlyn; Stilwell, Peter; Lane, Jennifer; Andrews, Cynthia; Dutton, Tanya; Ferkol, Doug; Harris, Jonathan; Houk, Shauna; Pendergast, Noel; Persaud, David; et al. (Journal of Interprofessional Care)
Interprofessional simulation-based education (IP-SBE) supports the acquisition of interprofessional collaborative competencies. Psychologically safe environments are necessary to address socio-historical hierarchies and coercive practices that may occur in IP-SBE, facilitating fuller student participation. A scoping review was conducted to understand the barriers and enablers of psychological safety within IP-SBE. Research papers were eligible if they included two or more undergraduate and/or post-graduate students in health/social care qualifications/degrees and discussed barriers and/or enablers of psychological safety within simulation-based education. Sources of evidence included experimental, quasi-experimental, analytical observational, descriptive observational, qualitative, and mixed-methodological peer-reviewed studies. English or English-translated articles, published after January 1, 1990, were included. Data were extracted by two members of the research team. Extraction conflicts were resolved by the principal investigators. In total, 1,653 studies were screened; 1,527 did not meet inclusion criteria. After a full-text review, 99 additional articles were excluded; 27 studies were analyzed. Psychological safety enablers include prebriefing-debriefing by trained facilitators, no-blame culture, and structured evidenced-based simulation designs. Hierarchy among/between professions, fear of making mistakes, and uncertainty were considered barriers. Recognition of barriers and enablers of psychological safety in IP-SBE is an important first step towards creating strategies that support the full participation of students in their acquisition of IPC competencies.